Characterization of Colletotrichum sublineolum Isolates Causing Sorghum Anthracnose and Screening Sorghum Cultivars for their Reaction to the Disease - Gebremariam, Elfinesh Shikur (Journal of Science and Development, 2025)
Anthracnose, caused by Colletotrichum sublineolum is an important disease of sorghum in Ethiopia. Assessing variability in a pathogen population and screening host genotypes against a particular disease is an important step in devising a sound disease management strategy. This study was aimed to characterize C. sublineolum isolates from three selected sorghum-growing districts (Haramaya, Kersa, and Girawa) of East Hararghe and evaluate sorghum cultivars’ reaction against the disease. Infected leaf samples were collected from the three districts during 2022 cropping seson. A total of 31 Colletotrichum sublineolum isolates were examined for their morphological and cultural traits; 11,10, and 10 isolates were from Girawa, Kersa and Haramaya districts, respectively. Cultural and morphological characteristics of C. sublineolum isolates were studied by growing them on potato dextrose agar at 25 oC. Virulence of the 31 isolates was determined in three reference sets of sorghum genotypes with a detached leaf assay following a standard procedure.  Twenty released sorghum cultivars and three rating reference sets of sorghum genotypes were screened in net house and laboratory conditions. The C. sublineolum isolates showed variation in cultural and morphological characteristics. The isolates had largely gray to light gray colony color on the upperside. The colony growth ranged from 14.50 mm to 42.33 mm. The conidial length and width ranged from 4.97 to 25.74 µm and 2.44 to 4.07 µm, respectively, with oval and falcate shapes. The virulence level varied significantly among the isolates tested. Isolates HA7A, HA3A, HA5A, HA6B, KD8C, KD8D and GM9B had higher virulence, while isolates GM2A HA1A HA4A, and KD4D had lower virulence levels on reference sorhum genotypes. The sorghum cultivars tested had significantly different responses to C.sublineolum. Cultivars Dekeba, Tilahun, Abshir, and Argity were identified as resistant to anthracnose disease. The finding of this study might be useful for breeding sorghum varieties for anthracnose resistance.